2022
DOI: 10.3390/ijerph19020731
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Human Health Risk Assessment of Heavy Metals in Paddy Plants Collected from Perak, Malaysia

Abstract: Rice is one of the major crops as well as the staple food in Malaysia. However, historical mining activity has raised a concern regarding heavy metal contamination in paddy plants, especially in Perak, a state with major tin mining during the late nineteenth century. Therefore, the objective of this study is to investigate the heavy metals (As, Cd, Pb, Cu, Cr) contamination in paddy soils and paddy plants in three districts in Perak. The content of heavy metals was determined using ICP-MS, while the absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Sibuar [16] et al conducted a quantitative analysis and human health risk assessment of HM contamination in rice soils and rice plants in three regions of Perak, Malaysia, and their findings indicated that HM contamination poses a potential health risk to the population and requires control measures. Raja [17] et al evaluated the health risk of HMs in the groundwater of industrial townships in India, and the high carcinogenic and noncarcinogenic risk values indicated the presence of health risks from lead, cadmium, nickel, and chromium metals in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Sibuar [16] et al conducted a quantitative analysis and human health risk assessment of HM contamination in rice soils and rice plants in three regions of Perak, Malaysia, and their findings indicated that HM contamination poses a potential health risk to the population and requires control measures. Raja [17] et al evaluated the health risk of HMs in the groundwater of industrial townships in India, and the high carcinogenic and noncarcinogenic risk values indicated the presence of health risks from lead, cadmium, nickel, and chromium metals in the study area.…”
Section: Introductionmentioning
confidence: 99%